In silico study of RKD4 gene function in Coffea arabica L. and various cultivated plants related to embryo formation initiation - Arimarsetiowati, Rina; Semiarti, Endang; Daryono, Budi Setiadi; Astuti, Yohana Theresia Maria; Prastowo, Erwin (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
Arabica coffee supplies 60% of world coffee production because has a unique taste as superior quality beverage. Arabica coffee micropropagation can be conducted by somatic embryogenesis technique which produce clonal, fast dan uniform plant. The somatic embryogenesis (SE) process describes the integration of endogenous signals and gene reprogramming, which releases signals to initiate embryogenic processes. The use of endogenous auxin, either alone or in combination with other PGRs or stress, induces differential gene expression, which modifies the genetic program of somatic cells and regulates the transition to each stage during SE development. The RKD4 gene (RWP-RK DOMAIN-4) is a gene that plays a role in early initiation embryo formation and development. The characterization of RKD4 genes in C. arabica is still limited and under explored. The objective of this research is to explore the characteristics of RKD4 gene by comparing the difference and similarity of RKD4 gene in C. arabica and other cultivated plants. The method was initiate by identifying nucleotide sequences from the National Center for Biotechnology Information (NCBI) database. Furthermore, consists of analysis of nucletide alignment, alignment of amino acid sequences, protein analysis, protein motif functions discovery, analysis of phylogenetic tree, protein 2D and 3D-modelling and physiochemical properties. According to the analysis, there were 100 polymorphism points with a total number of mutations of 211 points. The phylogenetic tree show C. arabica L. has a very close relationship with grapes (Vitis vinivera) based on the RKD4 protein, gene structures and protein motifs. There are nine highly conserved motifs found in the protein alignment. C. arabica L. had more methyl jasmonate element responses than A. thaliana. The findings are useful to understand the intitiation of embryo formation mechanisms of C. arabica L and other cultivate plants during propagation through somatic embryogenesis in the long run.